Cover Image. (16th October 2019) - Pang, Hui; Zhang, Xu; Yang, Junjie; Shang, Yuting
Abstract : The cover image is based on the RESEARCH ARTICLE Adaptive backstepping ‐ based control design for uncertain nonlinear active suspension system with input delay by Hui Pang et al., https://doi.org/10.1002/rnc.4695 .